2019
DOI: 10.5603/fm.a2018.0078
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, number and topography of Wormian bones in Greek adult dry skulls

Abstract: The current study highlights a high incidence of WBs in a Greek population, indicating racial variation. The in depth knowledge of exact location, frequency and number of WBs is essential for clinicians intervening in the skull area, anthropologists and forensic surgeons investigating child abuse cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 23 publications
(55 reference statements)
7
32
1
Order By: Relevance
“…And the majority of wormian bones were sited at lambdoid suture (44.6 %), at coronal suture (39.8 %), at asterion (21 % on left, 13.9 % on right), at parietomastoid suture (15.1 % on left, 13.9 on right). Moreover, wormian bones were not found at occipitomastoid, sagittal sutures, bregma, lambda, pterion (Natsis et al, 2019). When we analyzed these results, it was seen obviously that the majority of wormian bones were seen at lambdoid suture like it was the case in our study.…”
Section: Discussionsupporting
confidence: 68%
“…And the majority of wormian bones were sited at lambdoid suture (44.6 %), at coronal suture (39.8 %), at asterion (21 % on left, 13.9 % on right), at parietomastoid suture (15.1 % on left, 13.9 on right). Moreover, wormian bones were not found at occipitomastoid, sagittal sutures, bregma, lambda, pterion (Natsis et al, 2019). When we analyzed these results, it was seen obviously that the majority of wormian bones were seen at lambdoid suture like it was the case in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Because asterion is a surgical landmark for transverse sinus surgery, its variations were studied many times by researches. Asterion is one of the sites including Wormian bones which vary in shape, size and number (6,11,12,13). Neurosurgeons should be careful when forming burr hole during posterolateral surgical approach to cranium because of the high incidence of Wormian bones in asterion (6).…”
Section: Discussionmentioning
confidence: 99%
“…Wormian bones are small ossicles which vary in shape, size and number. They are found along fontanelles and sutures (6). Asterion morphology is classified in two types in terms of presence of Wormian bones.…”
Section: Introductionmentioning
confidence: 99%
“…[18] A similar study in Greek revealed 124 skulls (74.7%) having Wbs out of total 166 skulls, with no difference of gender and age. [19] In Nigeria based study, 22 skulls were examined, with incidence of Wbs in 45.46% and maximum incidence in lambdoid suture. [20] The orifices due to small Wbs may sometimes be medico-legally misinterpreted as gunshot wound or vice versa.…”
Section: Discussionmentioning
confidence: 99%